Integrating Artificial Intelligence into Strategic Leadership: Implications for Ethical Governance, Employee Trust, and Organizational Performance in Indonesia - Safina, Wan Dian; Hutasuhut, Julianto; Pratama, Nugraha; Mulyono, Hardi; Rahmat, Muhammad (Yayasan Sinergi Kawula Muda, 2026)
Artificial intelligence (AI) is transforming strategic leadership, yet existing research in Indonesia has not systematically integrated how AI-enabled leadership, ethical governance, and employee trust are jointly represented across national policy, academic, and practitioner discourse. This study addresses this gap through a qualitative document analysis of a purposively assembled corpus of 42 Indonesian documents (2019–2025), including national policies (n=5), sectoral guidelines (n=4), academic articles (n=18), practitioner reports (n=10), and legal commentaries (n=5). Documents were retrieved via Google Scholar, institutional websites (Kominfo, OJK), and consultancy repositories using keywords: